2020
DOI: 10.1051/e3sconf/202020203028
|View full text |Cite
|
Sign up to set email alerts
|

Migration, environment, and country safety: analysis of touchpoints

Abstract: This study presents the results of bibliometric analysis of publications that are thematically related to migration, environment, and safety. Vosviewer software helped to analyze the co-use of keywords in these publications, and the authors' affiliation to specific countries was performing. The works for the period 1965-2019, indexed by the scientometric database Scopus, were taken for analysis. With the help of Scopus analytical resources, and analysis of the dynamics of publication activity on the research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Besides, some traditional socio-economic factors are determinants of regions' vulnerability to . The article studies the migration phenomenon and its linkages on fiscal revenues and budget expenditures with social benefits (Cristea et al, 2019;Levchenko et al, 2017;Didenko et al, 2020b). The research (Osabohien et al, 2020;Rajan, 2018;Shammi et al, 2020) showed that social protection positively affects employers' health and work outcomes through various channels, namely, building human resources and equity, the use of public resources, social inclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, some traditional socio-economic factors are determinants of regions' vulnerability to . The article studies the migration phenomenon and its linkages on fiscal revenues and budget expenditures with social benefits (Cristea et al, 2019;Levchenko et al, 2017;Didenko et al, 2020b). The research (Osabohien et al, 2020;Rajan, 2018;Shammi et al, 2020) showed that social protection positively affects employers' health and work outcomes through various channels, namely, building human resources and equity, the use of public resources, social inclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The environmental component is an integral part of sustainable development, the impact of which is greatly enhanced due to the extensive use of fossil resources and insufficient environmental protection. Uncontrolled pollution of territories can lead to economic consequences and negatively impact the environment [7,8], causing ecological disasters and migration of the working population [9,10]. At the same time, the Paris Agreement 2015 contains regulated requirements that disturb the transformation of energy balances in terms of reducing the share of coal [11,12] and expanding green energy production in the energy sector [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several scientists studied the development of the smart grid [34][35][36], environmental management, and green marketing (branding) [37][38] as crucial tools for improving the national economic energy efficiency in the process of carbon-free development.…”
Section: Introductionmentioning
confidence: 99%